Upaya Pemberantasan Tindak Pidana Perdagangan Orang pada Pekerja Migran Indonesia (Eradication of Human Trafficking Crimes among Indonesian Migrant Wrokers) - Nola, Luthvi Febryka (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2023)
One form of human trafficking crimes (TPPO) involves enticing individuals with promises of working abroad as Indonesian Migrant Workers (IMWs). In 2022–2023, there is an expected increase in the number of IMWs who fall victim to TPPO. These victims include those with low education and those with higher education and skills. They become targets of online and fraudulent job vacancies, particularly online scamming via social media. This paper aims to address the efforts to eradicate TPPO against IMWs, the factors that impede theseanti-trafficking endeavors, and strategies to expedite the eradication process. The research utilizes a normative juridical approach combined with qualitative descriptive analysis. From the discussion, it is apparent that anti-TPPO efforts against IMWs revolve around improving regulations, enforcing the law, enhancing facilities,raising public awareness, and altering the culture of illegal employment. Nevertheless, these efforts encounter obstacles stemming from unclear and weak regulations, a lack of professionalism among law enforcement officials, coordination deficiencies, limited resources and facilities for assistance, a lack of public knowledge, and a pervasive culture that supports such activities. These five factors can be addressed through legal reform, decisive actions, competent funding and data management, increased public education, and cultural change. Notably, these endeavors cannot be accomplished solely by the government; the DPR must contribute through its three functions: legislation, oversight, and budgeting. AbstrakSalah satu modus tindak pidana perdagangan orang (TPPO) adalah dengan menawarkan pekerjaan di luar negeri menjadi pekerja migran Indonesia (PMI). Pada tahun 2022–2023 terjadi peningkatan jumlah PMI yang menjadi korban TPPO. PMI korban TPPO tidak hanya yang berpendidikan rendah akan tetapi juga berpendidikan dan memiliki skill. Mereka menjadi korban melalui skema online scaming yaitu penipuan lowongan kerja melalui media sosial. Oleh karenanya, tulisan akan membahas upaya pemberantasan TPPO terhadap PMI, faktor yang menghambat upaya pemberantasan dan upaya yangdapat dilakukan untuk mempercepat pemberantasan. Penelitian ini menggunakan pendekatan yuridis normatif dan analisis deskriptif kualitatif. Dari pembahasan diketahui bahwa upaya pemberantasanTPPO terhadap PMI dilakukan melalui upaya perbaikan aturan, penegakan hukum, peningkatan sarana dan fasilitas, peningkatan kesadaran masyarakat dan perubahan budaya bekerja secara ilegal. Hanya saja upaya tersebut terhambat oleh adanya ketidakjelasan dan kelemahan aturan; kurang kredibilitas aparat dan minimnya koordinasi; terbatasnya fasilitas dan sarana penanganan; kurangnya pengetahuan masyarakat; serta kuatnya budaya pendukung. Kelima faktor ini dapat diatasi dengan cara pembaharuan hukum, penindakan tegas, manajemen pendanaan dan pendataan yang mumpuni, serta peningkatan edukasi pada masyarakat dan perubahan budaya. Kelima upaya ini tidak dapat dilakukan oleh pemerintah semata, DPR perlu membantu melalui tiga fungsi yang dimiliki yaitu legislasi, pengawasan, dan anggaran.